KAFE BUKU SEBAGAI RUANG LITERASI BUDAYA: STUDI KASUS “KAFE BUKUKU LAWAS” DALAM MASYARAKAT BERAGAM - Andrea Dhiya Nasywa Andini; Umi Kholifatul Latifah; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
This research discusses the role of Kafe BukuKu Lawas as a cultural literacy space in a diverse society, especially among students. The café combines the concepts of a coffee shopand a library to create a learning atmosphere that is comfortable, fun and supports a reading culture. This study uses a qualitative method with a case study approach. The data collection methods were interviews, documentation, and questionnaires involving 7 visitors out of all visitors at BukuKu Lawas Cafe. The results show that although visitors spend more time socializing or discussing, the presence of books and literacy activities initiated by visitors and the local community, such as book reviews, still contribute to increasing literacy awareness in the wider community. Factors such as the proximity to the university, the supportive atmosphere and access to books are the main attractions. However, there are still challenges in attracting more active reading interest from visitors. Therefore, there is a need to improve the quality of collection arrangement and consistency of literacy activities to strengthen the café's role as a cultural literacy space.